Faith-based mediation: A comparative perspective on the application of Sulh and Ho’oponopono - Mohd. Zain, Nor Razinah; Ahmadi, Faisal; Sautunnida, Lia (Faculty of Syariah and Law, Universiti Sains Islam Malaysia (USIM), 2019)
The application of mediation can be traced in many culture and tradition across the world. Closely related to the faith of the people, mediation has essential roles in resolving disputes among the members of society. While the faith-based mediation of Ho’oponopono is famous in Hawaii, the faith-based mediation of Sulh is famous among Muslims in South East Asia. The dispute resolution strategies which are used in Ho’oponopono and Sulh are comparatively analyzed in this research. The practices of Sulh are evaluated based on empirical findings collected from Pasir Mas (Kelantan, Malaysia) and Indragiri Hilir (Riau, Indonesia). Meanwhile, the qualitative findings on practices of Ho’oponopono are collected from earlier researches that utilized empirical investigations. By employing a qualitative doctrinal analysis, this research identifies similarities and differences of faith-based mediations of Sulh and Ho’oponopono. At the same time, the said faith-based mediations’ potentials and challenges are explored. Focusing on an expeditious resolution, it is found that faith-based mediations are still applied among the members of the society in Malaysia, Indonesia, and Hawaii.